"A Study of the Characteristrics of Hypokalemic Paralysis in Patient Hospitalized in Shahid Beheshti Hospital During 1990 -2000" - SA Masoud (Tehran University of Medical Sciences, 2001)
Hypokalemic disease is a disorder in which the amount of serum' s potassium declines and the patient faces limbs weakness. In this disease, eye muscle and respiratory muscles rarely become involved and death may follow due to respiratory paralysis and heart conducting disturbances. Since this disease is treatable and progressive weakness can be prevented, therefore in the study conducted we attempted to compare between the causes and epidemiological characteristics and start of clinical manifestation and the characteristics of this diseases with what had been presented in classical text and foreign sources in order to take effective measure for timely diagnosis. This was a descriptive prospective study. The records of hypocalemically paralyzed patients hospitalized in shahid Beheshti Hospital of Kashan during 1990 to 2000 were used to collect the data such as general condition of the patient, systematic and neurologic examination, serum potasium level, ABG, and paramedical measures like ECG were extracted and used for analysis. 27 patients were identified as Hypokalemic afflicted to paralysis and all were sporadic cases. The starting age for weakness attack was mostly in the second to fourth decade of life. The mean age for attack was 29 years . 96.3 percent were male and the rest were female. The level of potasium in serum of these patients during the weakness attack was mostly within 1 to 3.5 meq/L and the most changes in ECG was related to decrease in height at T and appearance of U- waves. 11 patients have more than 3 attacks (40.7 percent ), 10 patients faced all-attacks (37.3 percent) and 6 patients experienced 2 times attack (22 percent).Considering that hypokalemic paralysis disorder is a treatable disease and immediate diagnosis and treatment reduces cardiac and muscular problems, it is necessary for the physican who treat patients referring with flaccid paralysis to keep in mind four limbs of this disease and use diagnostic measures.